2013
DOI: 10.1002/pros.22675
|View full text |Cite
|
Sign up to set email alerts
|

ERG Overexpression and PTEN Status Predict Capsular Penetration in Prostate Carcinoma

Abstract: Background This study examines the combined effect of two common genetic alterations, ERG and PTEN, in prostate carcinoma progression. Methods Prostate tissue from ninety patients having unilateral capsular penetrating lesions (CPL), and a contra-lateral organ confined (COC) second lesion, were examined by immunohistochemistry for the expression of the TMPRSS2:ERG transformation product ERG and the loss of expression of PTEN, a powerful phosphatase inhibiting the PI3 Kinase pathway. Multivariate logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
(40 reference statements)
1
10
2
1
Order By: Relevance
“…Prior studies have reported that the lack of ETS gene fusions and lack of PTEN loss ( ERG wt/ PTEN wt) were associated with good prognosis in patients undergoing radical prostatectomy or in a conservatively treated watchful waiting cohort (3941). However those who were ERG +/ PTEN del had faster BCR rates in the prostatectomy cohort (41), whereas the ERG wt/ PTEN del patients had significantly lower survival rates than ERG +/ PTEN del patients in the watchful waiting cohort (31).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported that the lack of ETS gene fusions and lack of PTEN loss ( ERG wt/ PTEN wt) were associated with good prognosis in patients undergoing radical prostatectomy or in a conservatively treated watchful waiting cohort (3941). However those who were ERG +/ PTEN del had faster BCR rates in the prostatectomy cohort (41), whereas the ERG wt/ PTEN del patients had significantly lower survival rates than ERG +/ PTEN del patients in the watchful waiting cohort (31).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the multifocal nature of prostate cancer is well- recognized and several studies have documented the interfocal heterogeneity of ERG rearrangements in PCa harboring multiple tumor foci[11],[12] [13]. Hence genetically distinct tumor foci within the same patient are not unusual.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is also known to express variable levels of several markers associated with disease progression, such as phosphatase tensin homolog (PTEN) and ETS-Related Gene (ERG), making it a viable target for testing this procedure. A link between the PTEN pathway and ERG protein expression has previously been evaluated in various prostate cancer studies [8][9][10][11][12][13]. In studies investigating the trend of PTEN loss in tumors of prostatectomies and locally recurring castrate-resistant prostate cancers (CRCPs) with ERG overexpression, the data showed that the loss of PTEN was significantly associated with ERG positivity [11].…”
Section: Experimental Designmentioning
confidence: 99%